1D Amorphous Tungsten‐Based Ternary Refractory Metal Sulfides for Catalytic Hydrogen Evolution at Soft Interfaces. Issue 12 (7th November 2019) - Aslan, Emre; Sarilmaz, Adem; Ozel, Faruk; Hatay Patir, Imren; Girault, Hubert H.
Abstract: Transition metals incorporated into molybdenum sulfide and tungsten sulfide matrixes are promising candidates for hydrogen evolution due to the unique chemical and physical properties. Here, we first describe a general strategy for the synthesis of rod‐like ternary refractory metal sulfides (MWSx ; M=Ni, Co, Fe and Mn) through a simple hot‐injection method. The newly developed materials are affirmed as valuable alternatives to noble metal Pt due to their simple fabrication, inexpensive and impressive catalytic performance. We present that highly efficient catalysts for the hydrogen evolution at a polarized water/1, 2‐dichloroethane (DCE) interface by using the decamethylferrocene (DMFc). Kinetics of hydrogen evolution studies are monitored by two phase reactions using UV/Vis spectroscopy, and also further proved by gas chromatography. These ternary refractory metal sulfide catalysts show high catalytic activities on hydrogen evolution comparable to platinum. The rate of hydrogen evolution for the MWSx catalysts changed in the order Ni>Co>Fe>Mn according to the type of first row transition metals. Abstract : 1D amorphous tungsten‐based ternary metal sulfides (MWSx ; M=Ni, Co, Fe and Mn) have been synthesized by a hot injection method to minimize reaction time and pressure. The synthesized MWSx catalysts have been used in the catalytic hydrogen evolution reaction at the water/DCE soft interface by organic electron donor DMFc for the first time. The Ni and Co including catalyst shows better catalytic activities due to the relationship between hydrogen binding energy and electron withdrawing properties.